Transabdominal approach assisted by thoracoscopic drainage for lower esophageal perforation. (1st December 2015) - Maki, Harufumi; Azuma, Masaki; Kanamaru, Hitoshi; Nishiyama, Motohiro; Okamoto, Kazuya; Shimamura, Takahiro; Kyo, Kennoki; Maema, Atsushi; Nakamura, Toshio; Shirakawa, Motoaki; Yokoyama, Hidetaro
Abstract : The effectiveness of use of thoracoscopy for esophageal perforation has not been fully evaluated. We herein report a case of esophageal perforation for which a transabdominal approach assisted by thoracoscopic drainage was performed.